(untitled) - Nonaka, Ikujiro (New York, 1995)
How have Japanese companies become world leaders in the automotive and electronics industries, among others? What is the secret of their success? Two leading Japanese business experts, Ikujiro Nonaka and Hirotaka Takeuchi, are the first to tie the success of Japanese companies to their ability to create new knowledge and use it to produce successful products and technologies. In The Knowledge-Creating Company, Nonaka and Takeuchi provide an inside look at how Japanese companies go about creating this new knowledge organizationally.
Keywords: Communication in organizations,Industrial management,Truyền thông trong tổ chức,Quản trị công nghiệp; Japan,Japan,Nhật Bản,Nhật Bản